2009
DOI: 10.1159/000242362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhaled Corticosteroids on Metalloproteinase-8 and Tissue Inhibitor of Metalloproteinase-1 in the Airways of Asthmatic Children

Abstract: Background: The effects of corticosteroids on the level and expression of matrix metalloproteinase-8 (MMP-8; collagenase-2) and tissue inhibitors of metalloproteinases (TIMPs) in airway tissue are poorly characterized in vivo. Methods: We compared MMP-8 and TIMP-1 levels in induced sputum and their expression in airway inflammatory cells of healthy children (n = 27) and of children with newly diagnosed asthma with mild (n = 20) or moderate symptoms (n = 19), before and after 6 months of treatment with inhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
11
0
1
Order By: Relevance
“…This finding is consistent with research in other respiratory diseases, including CF, asthma, chronic obstructive pulmonary disease, and chronic bronchitis (19,(22)(23)(24)(25).…”
Section: Original Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with research in other respiratory diseases, including CF, asthma, chronic obstructive pulmonary disease, and chronic bronchitis (19,(22)(23)(24)(25).…”
Section: Original Researchsupporting
confidence: 91%
“…MMPs also have a diverse role in immunity that is not directly related to ECM modulation, including activation of cytokines, facilitation of cell migration, and activation of defensins (17). The ratios of individual MMPs to TIMPs have been reported to be informative in a number of other respiratory infections and diseases (18)(19)(20)(21)(22)(23)(24)(25); however, they have not been explored in bronchiectasis.…”
mentioning
confidence: 99%
“…In addition, Hoshino et al [22] reported that by reducing MMP-9 and increasing TIMP-1, corticosteroid treatment decreased the accumulation of subepithelial collagen in asthmatics. In another study [23] showed that inhaled budesonide normalized MMP-8/TIMP-1 ratio by reducing MMP-8 and increasing TIMP-1 in asthmatic children. In contrast to all above studies, all steroid treatment modalities had no effect on the levels of MMP-9 and TIMP-1 in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, MMP-13 levels were not detected in most of both healthy subjects and CAD patients [5, 29]. Corticosteroids were shown to repress the expression of MMP-8 [40]. Corticosteroids decreased MMP-8-positive eosinophils and macrophages and at the same time upregulated TIMP-1 from macrophages protecting the proteolytic effect of MMP-8 in the airways of asthmatic children [40].…”
Section: Collagenases (Mmp-1 Mmp-8 Mmp-13 and Mmp-18)mentioning
confidence: 99%
“…Corticosteroids were shown to repress the expression of MMP-8 [40]. Corticosteroids decreased MMP-8-positive eosinophils and macrophages and at the same time upregulated TIMP-1 from macrophages protecting the proteolytic effect of MMP-8 in the airways of asthmatic children [40]. Glucocorticoid treatment downregulates the inflammatory genes through the activation of the glucocorticoid receptor, inhibits the cell expression of MMPs and activates the cellular expression of TIMPs.…”
Section: Collagenases (Mmp-1 Mmp-8 Mmp-13 and Mmp-18)mentioning
confidence: 99%